2003
DOI: 10.1152/ajpheart.00447.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular mechanisms activated by microinjection of baclofen into NTS of conscious rats

Abstract: The peripheral mechanisms responsible for pressor response produced by microinjections of baclofen (GABAB agonist) into the nucleus tractus solitarii (NTS) of conscious rats were studied. Bilateral microinjections of baclofen (10-1,000 pmol/100 nl) produced a dose-related increase in mean arterial pressure (MAP) and heart rate. The maximal response was observed after 15 min. Intravenous injection of prazosin decreased MAP to control levels. Subsequent treatment with Manning compound (vasopressin receptor antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
6
1
1
Order By: Relevance
“…The notion that this pathway is involved is supported by the current observations that microinjection of baclofen into the NTS increases renal sympathetic nerve activity in both SHR and WKY rats and that the sympathoexcitatory response to baclofen is enhanced in SHR. This hypothesis is also supported by studies from other research groups that show the pressor response to baclofen microinjected into the NTS is attenuated by a vasopressin antagonist (20). In addition, the NTS is well known as a termination site for primary afferent fibers from baroreceptors and other peripheral cardiovascular receptors that contain blood pressure-sensitive neurons.…”
Section: Discussionsupporting
confidence: 65%
“…The notion that this pathway is involved is supported by the current observations that microinjection of baclofen into the NTS increases renal sympathetic nerve activity in both SHR and WKY rats and that the sympathoexcitatory response to baclofen is enhanced in SHR. This hypothesis is also supported by studies from other research groups that show the pressor response to baclofen microinjected into the NTS is attenuated by a vasopressin antagonist (20). In addition, the NTS is well known as a termination site for primary afferent fibers from baroreceptors and other peripheral cardiovascular receptors that contain blood pressure-sensitive neurons.…”
Section: Discussionsupporting
confidence: 65%
“…During exercise, Potts et al (45) showed that electrically evoked muscular contraction inhibits arterial baroreceptor signaling within the nucleus of the tractus solitarius (NTS) via activation of GABAergic receptors in rats, suggesting that skeletal muscle afferents are a potential source of synaptic drive to GABAergic neurons within the NTS. Indeed, GABA activation in conscious rats induces pressor response and tachycardia (8,31). However, the extent to which these findings can be extrapolated to humans remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-NTS microinjections of GABA produce an increase in blood pressure and heart rate, which can also be evoked by microinjections of GABA A as well as GABA B receptor agonists into this nucleus [10,15,51,102,198,199,201]. It has been proposed that GABA A/B receptor-mediated pressor responses are due to an attenuation of the processing of baroreflex messages [51].…”
Section: Gabamentioning
confidence: 99%